How Side Effects Can Be Positive. A Reading of Beck’s Metamorphosis - D'Andrea, Fabio (Italian Sociological Review, 2022)
In this essay I will contend that Beck’s idea of metamorphosis fits within the complex model of human evolution on which I am working and aptly describes what is happening to Western culture. What is currently beginning to crumble is the primordial paradigm – what I define the Ur-Paradigma, a set of generative cultural traits whence issues most of the form and trajectory of a given culture – that has influenced and (mis)directed the course of history so far. This leaves us without tools or theoretical frameworks that are up to the task of understanding the sense and direction of global events. The withering of the Weltbild brings to light a few of the items of the Ur-Paradigma and the bias they lent to some crucial representations on which we built the world we live in: the “birth of Athena” representation of Man as a creature that appeared perfect and immutable out of the blue, instead of being the fruit of an age-long evolution; the idea of knowledge as an unchangeable given, universal and objective. Only within such a perspective must side effects be conceived of as necessarily negative, as they represent a mistake in the otherwise flawless human planning. They should instead be thought of as the logical issue of the reductive process that leads to knowledge, leaving an essential gap between what we know and ‘the meaningless infinity of events in the world’ (Weber). [...]